Scoping Review: Interprofessional Simulation as an Effective Modality to Teaching Interprofessional Collaborative Competencies in the Emergency Department - Barton, Lily; Lackie, Kelly; Miller, Stephen G. (Journal of Research in Interprofessional Practice and Education, 2023)
Background: A scoping review was conducted to map the current body of research pertaining to simulation-enhanced interprofessional education (Sim-IPE) as a modality for teaching interprofessional collaboration (IPC) in the emergencydepartment (ED). Methods and Findings: The research team followed the PRISMA Extension for Scoping Reviews framework. Studies were included if they involved two or more healthcare professions, utilized simulation as the learning method for interprofessional education (IPE), involved simulation pertaining to the ED, and identified at least one Canadian Interprofessional Health Collaborative or Interprofessional Education Collaborative IPC competency as a learning outcome. In total, 896 studies were included for title and abstract screening and 806 were deemed irrelevant. Ninety full-text studies were assessed for eligibility and 34 were included in the review. Conclusions: Eighteen studies found Sim-IPE to be an effective method for teaching interprofessional competencies in the ED. Simulation-enhanced interprofessional education appears to be a promising methodology for teaching IPC competencies to ED healthcare professionals. Interprofessional collaboration competency frameworks should be utilized to guide Sim-IPE, and assessment tools specific to interprofessional competencies should be used in the assessment phase of Sim-IPE. Faculty development is a crucial component of Sim-IPE. Further longitudinal and outcome-based research is required.